PENGARUH PENDEKATAN KONSTRUKTIVISTIK TERHADAP PEROLEHAN BELAJAR PENDIDIKAN KEWARGANEGARAAN SD - Budiyansyah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The influence of the Constructivist approach on the learning acquisition of PKN students class V. This study aims to find out how big the influence of the talking stick model on the acquisition of PKN learning. The method used in this research is experimental method, with nonequivalen control group design. Collecting technique is measurement technique. Based on acquisition of data analysis, the mean of learning acquisition of student of control class equal to 80,88 while experiment class equal to 85,37. The acquisition of hypothesis test (t-test) using t-test pollad variance was obtained t count of 3,11 and t table 2,000 (significance level (Î±) = 5% and dk = 61) showed that tcount is greater than ttable then Ha is accepted. From the calculation of Effect size, obtained 0.76 (medium criteria) This means Constructivist approach gives a high influence on the learning outcomes of five grade students of Elementary School 34 South of Pontianak. Â  Keywords : Influence, Constructivist approach, Learning Acquisition